ENERGY RECOVERY FROM MUNICIPAL SOLID WASTE: OPPORTUNITIES AND CHALLENGES IN THE BRAZILIAN SCENARIO - Pilissão, Y. L.; Machado, A. G.; Virmond, E.; Watzko, E. S. (Revista de Engenharia Térmica, 2021)
Municipal solid waste has always been an undesirable asset in society, and its generation grows every year. Inadequate waste disposal may cause many problems, either by the contamination of the environment or by its capacity to serve as a vector for a series of pathogenic elements. The COVID-19 pandemic drew the world’s attention to these challenges and made it clear how they impact society in an unprecedented way. The higher amount of waste and safety supplies discarded, such as masks and facial shields, require an analysis of the current situation of solid waste management along with solutions to increase the capacity for resource recovery. Methods of treating, collecting, transporting, and disposing of municipal solid waste must be integrated with the other levels of the waste hierarchy (prevention, reuse and preparing for reuse, recycling, other recovery (including energy recovery), and disposal). The scientific literature on this subject was verified in this paper, serving as a subsidy for the implementation of possible processes to be used in companies in the area of basic sanitation and city halls, which can benefit from investments that will incur in the generation of products of added value, creating a new link in its business chain. The production and application of integrated municipal solid waste management systems, including energy recovery from refuse derived fuel, can reduce the volume and expenses of municipal administrations with inadequate waste disposal in landfills and promote more sustainable practices in the circular economy scenario. Therefore, this paper sought to highlight the main activities related to municipal solid waste management with an aim to energy recovery.